Pengaruh Literasi Keuangan, Financial Technology dan Social Media Terhadap Kinerja Keuangan UMKM di Kota Padang - Kusuma, Riza Pipi; Afriyenti, Mayar (Universitas Negeri Padang, 2025)
This study seeks to address a deficiency in our comprehension of the impact of financial education, digital tools, and social media on the profitability of micro, small, and medium-sized enterprises (MSMEs) in Padang City. This pertains to quantitative research. Padang City had 47,692 micro, small, and medium-sized enterprises (MSMEs), with 100 participating in the survey. The criteria for MSMEs registered with the Padang City Cooperative and MSME Service include those owned and managed by the Community, which utilize technology-based payment facilities, employing the random sampling technique, also referred to as the random sampling method. This sampling method utilizes the probability sampling approach. One hundred micro, small, and medium-sized enterprises (MSMEs) registered with the Padang City Cooperative and MSME Service were comprehensively surveyed using questionnaires to collect primary data. This study utilized a combination of documentation and questionnaires for data compilation, employing multiple linear analysis as the analytical technique. This study determined that financial literacy positively and significantly influenced the financial performance of micro, small, and medium-sized enterprises (MSMEs) in Padang City. Financial technology and social media positively influenced the financial performance of MSMEs.